A new pathotype 93R57 (104-4) of Puccinia triticina on wheat from India - Bhardwaj, S C; Kumar, Subodh; Gupta, Neha; Sharma, Sangeeta (Journal of Cereal Research, 2011)
A new pathotype 93R57 of Puccinia triticina was identified in 2010 from district Solan of Himachal Pradesh, India. The new pathotype is close to the 104 group, however, is avirulent to Lr3. The new pathotype appears to be a case of reverse mutation for plr3 in the existing pathotype 21R63. Its avirulence/virulence structure and rust resistance sources are listed. This year it was identified in a sample from Uttarakhand.